The Influence of Learning Agility, Ambidexterity, and Organizational Climate on Employee Performance through Digital Transformation at the Financial and Development Supervisory Agency (BPKP) of North Sumatra Province - Rosari Oktoria Serena; Elisabet Siahaan; Beby Karina Fawzea Sembiring (Journal of Business Management, 2025)
Employee performance at the BPKP Representative Office of North Sumatra has not yet reached an optimal level, as indicated by several organizational targets that remain unmet. This challenge has become increasingly critical amidst the rapid acceleration of digital transformation, which demands strong learning agility, flexibility in work approaches, and the establishment of an organizational environment that supports change. This study aims to analyze the influence of Learning Agility, Ambidexterity, and Organizational Climate on Employee Performance, with Digital Transformation as a mediating variable, among employees at BPKP North Sumatra. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected from 125 active auditors through questionnaires developed based on validated theoretical dimensions and empirical indicators. The results indicate that Learning Agility and Organizational Climate are the most significant factors influencing employee performance. Digital Transformation also has a significant direct impact on employee performance and plays a strategic mediating role by linking individual and organizational characteristics to performance outcomes. This study contributes theoretically to the reinforcement of digital-based organizational behavior models and provides practical implications for human resource strategies, work culture development, and institutional policy in support of technology-driven bureaucratic reform. Future research is recommended to expand the study objects and adopt broader methodological approaches to generate more contextual and applicable insights.